Et felles overnattingssted for ravn Corvus corax i bruk gjennom ti vintre - Østbye, Eivind; Såtvedt, Olav (Ornis Norvegica, 2008)
A large communal roost for Ravens Corvus corax at Lauar, near the town of Kongsberg in Buskerud county, southern Norway, has been in use each winter between 1998 to 2008. The roost was used between mid-November to mid- April each year. At most around 400 Ravens spent the night here. They usually left early in the morning, and returned late in the evening just before sunset. Most of the birds flew to two garbage dumps some distance away (10 km and 20 km away).